2020
DOI: 10.1136/bmjspcare-2020-002242
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dementia on informal care: a systematic review of family caregivers’ perceptions

Abstract: IntroductionCaregivers play a major role in providing all the support and care in daily activities for their relatives with dementia. To fully describe the influence of dementia caregiving on family caregivers’ life, we conducted a systematic review including caregivers’ perceptions about the positive and negative aspects of caring and the expressed factors.Materials and methodsWe conducted a systematic review including articles from January 1998 to July 2020. Qualitative studies reporting family caregivers’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
158
3
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 97 publications
2
158
3
9
Order By: Relevance
“…FTD is marked by a gradual onset (Johannessen et al, 2017). Often family members may therefore misinterpret subtle symptoms as variations of a person's 6 NEEDS OF CARERS OF PEOPLE WITH FTD Recent reviews of the literature have reported that being aninformal carer for a person with dementia can lead to physical and psychological problems, social isolation and financial difficulties (Brodaty & Donkin, 2009;Chiao et al, 2015;Lindeza et al, 2020;Lindt et al, 2020). These areas of difficulty are often combined in the measurement of carer 'burden', which refers to the physical, financial and emotional strain experienced by a carer of a person with illness (Dunkin & Anderson-Hanley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…FTD is marked by a gradual onset (Johannessen et al, 2017). Often family members may therefore misinterpret subtle symptoms as variations of a person's 6 NEEDS OF CARERS OF PEOPLE WITH FTD Recent reviews of the literature have reported that being aninformal carer for a person with dementia can lead to physical and psychological problems, social isolation and financial difficulties (Brodaty & Donkin, 2009;Chiao et al, 2015;Lindeza et al, 2020;Lindt et al, 2020). These areas of difficulty are often combined in the measurement of carer 'burden', which refers to the physical, financial and emotional strain experienced by a carer of a person with illness (Dunkin & Anderson-Hanley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a worldwide lack of knowledge, awareness, and an indepth understanding of dementia impact on caregiver's daily life. Results from a recent review have shown that the negative aspects involved in informal caregiving prevail over positive, to caregivers, and that the high complexity of the experience of caring can only be reduced with multidirectional approach addressing these community's needs and improving the quality of life of the person with dementia and their family caregivers [27].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, studies have shown caregivers' different perceptions of their roles. Numerous investigations have demonstrated that informal caregivers suffered from psychological complications, depression, stress, and mental pressure (Chiao et al, 2015 ; Lindeza et al, 2020 ). Besides, nearly one-fourth of the caregivers of patients with Alzheimer's disease had anxiety (Mahoney et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%